Can integrated agriculture-nutrition programmes change gender norms on land and asset ownership?: Evidence from Burkina Faso - van den Bold, Mara; Dillon, Andrew; Olney, Deanna K.; Ouédraogo, Marcellin; Pedehombga, Abdoulaye; Quisumbing, Agnes R. (Taylor and Francis, 2015)
This article uses a mixed-methods approach to analyse the impact of an integrated agriculture and nutrition programme in Burkina Faso on women's and men's assets, and norms regarding ownership, use and control of assets. We use a cluster-randomised controlled trial to determine whether productive asset transfers and increased income-generating opportunities for women increase women's assets over time. Qualitative work on gender norms finds that although men still own and control most assets, women have greater decision-making power and control over home gardens and their produce, and attitudes towards women owning property have become more favourable in treatment areas.